PENERJEMAHAN LELUCON BERBAHASA INGGRIS DARI SITUS WWW.WORKJOKES.COM KE DALAM BUKU “BILA DOKTER, PETANI DAN MANAGER TERTAWA” - R. Pujo Handoyo; Slamet Riyadi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2009)
This paper investigates the translation of jokes from English into Indonesian in a book entitled “Bila Dokter, Petani dan Manager Tertawa” (BDPMT). The main objective is to identify and describe: 1) the strategies of translation, 2) the accuracy of the translation and 3) the humorousness of the translation. The investigation on the translation strategies of all data (55 jokes) identifies ten strategies namely addition of meaning, reduction of meaning, change of sentence structure, shift of focus, change of word’s connotative value, transference (borrowing), compensation of phonetic features, use of common TL equivalence, deviation of meaning and literal translation. Those strategies result in accurate (13%), fairly accurate (34%), less accurate (29%) and non-accurate (23%) translations. Meanwhile, the investigation on readers’ responses indicates that 52 % data stay humorous, whereas the rest 48 % become not humorous after the process of translation. Further analysis reveals a strong connection between the translation strategies, the accuracy of meaning and the humorousness of translation. The results of analysis show the significance of translation process which focuses on the equivalence of effects. This process should be started with an exploration to the humor ideas and their techniques of making, and ended with an evaluation to assure the accuracy of meaning.